The Effect of an Online Self-Care Training Program on Perceived Stress in COVID-19 Patients: A Randomized Control Trial - Arash Marzban; Zahra Farsi; Effat Afaghi; Mehdi Rezaei; Mohsen Moradi (Mashhad University of Medical Sciences, 2024)
Background: The coronavirus disease 2019 (COVID-19) caused many adverse effects, including increased stress in patients.Aim: The present study was conducted with aim to determine the effect of an online self-care training program on perceived stress in COVID-19 patients.Method: This randomized control trial study was fulfilled by recruiting 132 COVID-19 patients, referred to two hospitals in Isfahan, Iran, 2021. The patients were selected using the purposive sampling method and were then randomly allocated into experimental and control groups (n=63 in each group). The online self-care training program was presented to the experimental group in six 30-minute sessions over two weeks. The data were collected through an individual characteristic form and the Perceived Stress Scale (PSS) at three stages before, immediately, and one month after the intervention. P<0.05 was considered statistically significant.Results: The mean scores of perceived stress before, immediately, and one month after the intervention in the experimental group were 30.51±6.31, 24.59±4.66, and 26.57±3.82, respectively and in the control group were 29.78±4.81, 29.4±4.57, and 29.11±4.73, respectively. Moreover, no significant difference was observed between the two groups at the pre-intervention stage (p=0.467), while the mean scores of perceived stress in the experimental group were lower compared with the control group immediately (p<0.001) and one month after the intervention (p=0.001).Implications for Practice: The online self-care training program led to a reduction in perceived stress in COVID-19 patients. Thus, implementing this self-directed program may be considered as a safe and useful method to relieve perceived stress in similar conditions.